EXPOSURE PATHWAYS AND THE EFFECTS OF TRACE METALS AND POLYCYCLIC AROMATIC HYDROCARBONS (PAHS) ON HUMANS - Ogbuewu, Ifeanyi; Nnaji, Jude Chidozie (Unesa Journal of Chemistry, 2024)
ABSTRACT The various exposure pathways and health impacts of trace metals (TMs) and polycyclic aromatic hydrocarbons (PAHs) on humans were reviewed. They have been confirmed to be toxic and carcinogenic to humans, especially above safe limits. Various forms of industrial and domestic processes lead to the discharge of trace metals, PAHs, and their compounds in different forms such as gases, vapour, particulates, liquid waste, and solid waste into the air, water-bodies, and soil. TMs and PAHs are deposited in food through the combustion of fossil fuels, grilling of food at high temperatures, pan frying, and microwave methods of cooking. Some heavy metals like chromium, cadmium, and arsenic are said to cause cancer and genetic instability. The cancer-causing potential of PAH is a result of the metabolic transformation undergone by PAH in the human body which forms active metabolites that bind to DNA, a genetic material inside the cell. PAHs have been classified by the International Agency for Research on Cancer (IARC) of the World Health Organization (WHO) according to their degree of toxicity and carcinogenicity to humans. Avoiding contact of food with flames and cooking with the heat sources above rather than below food is the recommendation made by the Joint Expert Committee on Food Additives (JECFA) as a measure of PAH reduction.